Antibacterial and Antioxidant Activities of Novel Actinobacteria Strain Isolated from Gulf of Khambhat, Gujarat - Dholakiya, Riddhi N.; Kumar, Raghawendra; Mishra, Avinash; Mody, Kalpana H.; Jha, Bhavanath (Frontiers in Microbiology, 2017)
Bacterial secondary metabolites possess a wide range of biologically active compounds including antibacterial and antioxidants. In this study, a Gram-positive novel marine Actinobacteria was isolated from sea sediment which showed 84% 16S rRNA gene sequence (KT588655) similarity with Streptomyces variabilis (EU841661) and designated as Streptomyces variabilis RD-5. The genus Streptomyces is considered as a promising source of bioactive secondary metabolites. The isolated novel bacterial strain was characterized by antibacterial characteristics and antioxidant activities. The BIOLOG based analysis suggested that S. variabilis RD-5 utilized a wide range of substrates compared to the reference strain. The result is further supported by statistical analysis such as AWCD (average well color development), heat-map and PCA (principal component analysis). The whole cell fatty acid profiling showed the dominance of iso/anteiso branched C15–C17 long chain fatty acids. The identified strain S. variabilis RD-5 exhibited a broad spectrum of antibacterial activities for the Gram-negative bacteria (Escherichia coli NCIM 2065, Shigella boydii NCIM, Klebsiella pneumoniae, Enterobacter cloacae, Pseudomonas sp. NCIM 2200 and Salmonella enteritidis NCIM), and Gram-positive bacteria (Bacillus subtilis NCIM 2920 and Staphylococcus aureus MTCC 96). Extract of S. variabilis strain RD-5 showed 82.86 and 89% of 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging and metal chelating activity, respectively, at 5.0 mg/mL. While H2O2 scavenging activity was 74.5% at 0.05 mg/mL concentration. Furthermore, polyketide synthases (PKSs types I and II), an enzyme complex that produces polyketides, the encoding gene(s) detected in the strain RD-5 which may probably involve for the synthesis of antibacterial compound(s). In conclusion, a novel bacterial strain of Actinobacteria, isolated from the unexplored sea sediment of Alang, Gulf of Khambhat (Gujarat), India showed promising antibacterial activities. However, fractionation and further characterization of active compounds from S. variabilis RD-5 are needed for their optimum utilization toward antibacterial purposes.